(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
This article analyzes the international operations in the field of halal business, including the experience of countries such as Malaysia, Saudi Arabia, the United Arab Emirates, and Turkey. Also, the legal and institutional foundations, national standards and certification system, state programs and support measures in the field of halal business in Uzbekistan are highlighted. The main conclusions and suggestions for studying and adapting the international experience for Uzbekistan in the field of halal business have been formulated.